My say: make direct negotiations in public-private partnerships transparent - Ismail, Suhaiza (The Edge Communications Sdn Bhd, 2025)
As Malaysia continues its journey towards robust socioeconomic growth and governance reforms, a critical aspect of public sector management — the use of direct negotiations in public-private partnership (PPP) projects — has come under increased scrutiny. While such negotiations are often justified as a means of expeditious project implementation and maintaining close collaboration with the private sector, they have led to mounting public concerns about transparency, governance and fiscal responsibility.